PENGARUH PROFITABILITY, FIRM SIZE, DEFAULT RISK, VOLUNTARY DISCLOSURE TERHADAP EARNING RESPONSE COEFFICIENT - Linda Santioso; Lucky Suvia; Andreas Bambang Daryatno (Jurnal Akuntansi, 2020)
The purpose of this study is to determine the effect of profitability, firm size, default risk and voluntary disclosure on Earning Response Coefficient. The sample of this research use manufacuting company that listed in ISE for the period 2016-2018. Determination of the sample in this study using purposive sampling method and 145 data in three years. The dependent variable in this research is Earning Response Coefficient and independent variables are profitability, firm size, default risk and voluntary disclosure. Analysis tool that will be used to analyse the hypothesis with multiple linier regression modelis program SPSS 23. The result for this research showed that partially profitability has a significant effect on Earning Response Coefficient, while firm size, default risk, and voluntary disclosure do not have an effect on Earning Response Coefficient. Keywords: ERC, profitability, firm size, default risk, voluntary disclosure